Effect of intraoperative pressure ulcer preventive nursing on inflammatory markers in patients with high-risk pressure ulcers: A protocol of systematic review and meta-analysis. Issue 20 (15th May 2020) - Jin, Feng; Fu, Yan-jun; Zhang, Yang; Yan, Jing-ling; Zhou, Kui-chen; Liu, Hong-wei
Abstract: Background: This study will be designed to appraise the effects of intraoperative pressure ulcer preventive nursing (IPUPN) on inflammatory markers (IMs) in patients with high-risk pressure ulcers (HRPU) based on high quality randomized controlled trials (RCTs). Methods: In this study, we will perform a rigorous literature search from the following electronic databases: Cochrane Library, MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, and Chinese Biomedical Literature Database. All electronic databases will be retrieved from their initial time to March 1, 2020 without limitations of language and publication status. We will only consider high quality RCTs that explored the effects of IPUPN on IMs in patients with HRPU. Two investigators will identify relevant trials, extract data, and appraise risk of bias in each eligible trial. Data will be pooled by either a fixed-effects model or a random-effects model according to the results of heterogeneity identification. The primary outcomes include IMs, and incidence of new pressure ulcers. The secondary outcomes are time to ulcer development, quality of life, length of hospital stay, and adverse events. Statistical analysis will be undertaken using RevMan 5.3 software. Results: This study will summarize high quality clinical evidence of RCTs to evaluate the effects of IPUPN on IMs in patients with HRPU. Conclusion: The expected findings may provide helpful evidence to determine whether IPUPN is an effective intervention on IMs in patients with HRPU. INPLASY Registration Number: INPLASY202040029.